Battling the un-dead: the status of the Diptera genus-group names originally proposed in Johann Wilhelm Meigen’s 1800 pamphlet - Evenhuis, Neal L.; Pape, Thomas (Zootaxa, 2017)
The work of Meigen 1800 was suppressed by the ICZN Commission in 1963 for the purposes of zoological nomenclature. The work as such is still to be treated as having been published and it remains available as a source of published descriptions and illustrations. Therefore, while the names in Meigen (1800) are deemed unavailable, a subsequent usage of any of the names may be considered a novel proposal. We review the first post-Meigen 1800 occurrence of each name, its first date of availability and authorship, and determine status and synonymy.        Designations of type species are given for the following genus-group names: Coryneta Hendel, 1908 [Hybotidae]; Cyanea Hendel, 1908 [Hippoboscidae].        Acting as First Reviser, we select the following as the correct original spelling from multiple original spellings: Calirrhoe Hendel, 1908.        New synonymies are proposed for the following: Ablabesmyia Johannsen, 1905 under Pelopia Latreille, 1802, n. syn. [Limoniidae]; Amasia Meigen in Hendel, 1908 under Penthetria Meigen, 1803, n. syn. [Bibionidae]; Amphinome Meigen in Hendel, 1908 under Limonia Meigen, 1803, n. syn. [Limoniidae]; Antiopa Meigen in Hendel, 1908 under Chrysotoxum Meigen, 1803, n. syn. [Syrphidae]; Apivora Meigen in Hendel, 1908 under Volucella Geoffroy, 1762, n. syn. [Syrphidae]; Atalanta Meigen in Hendel, 1908 under Clinocera Meigen, 1803, n. syn. [Empididae]; Calirrhoe Meigen & Hendel in Hendel, 1908 under Prosena Le Peletier & Audinet-Serville, 1828, n. syn. [Tachinidae]; Chrysozona Hendel, 1903 under Haematopota Meigen, 1803, n. syn. [Tabanidae]; Cinxia Meigen in Hendel, 1908 under Sericomyia Meigen, 1803, n. syn. [Syrphidae]; Cleona Meigen in Hendel 1908 under Callomyia Meigen, 1804, n. syn. [Platypezidae]; Clythia Hendel, 1903 under Platypeza Meigen, 1803, n. syn. [Platypezidae]; Coryneta Meigen in Hendel, 1908 under Tachydromia Meigen, 1803, n. syn. [Hybotidae]; Crocuta Bezzi, 1907 under Siphona Meigen, 1803, n. syn. [Tachinidae]; Cyanea Meigen in Hendel, 1908 under Melophagus Latreille, 1802, n. syn. [Hippoboscidae]; Cypsela Meigen in Hendel, 1908 under Sphaerocera Latreille, 1804, n. syn. [Sphaeroceridae]; Dionnaea Meigen in Hendel, 1908 under Rhamphomyia Meigen, 1822, n. syn. [Empididae]; Dorilas Meigen in Hendel, 1908 under Pipunculus Latreille, 1802, n. syn. [Pipunculidae]; Echinodes Meigen in Hendel, 1908 under Eriothrix Meigen, 1803, n. syn. [Tachinidae]; Erinna Hendel, 1903 under Xylophagus Meigen, 1803, n. syn. [Xylophagidae]; Eulalia Hendel, 1903 under Odontomyia Meigen, 1803, n. syn. [Stratiomyidae]; Euphrosyne Meigen in Hendel, 1908 under Macrocera Meigen, 1803, n. syn. [Keroplatidae]; Flabellifera Osten Sacken, 1882 under Tanyptera Latreille, 1804, n. syn. [Tipulidae]; Fungivora Meigen in Hendel, 1908 under Mycetophila Meigen, 1803, n. syn. [Mycetophilidae]; Helea Osten Sacken, 1882 under Ceratopogon Meigen, 1803, n. syn. [Ceratopogonidae]; Hermione Bezzi, 1908 under Oxycera Meigen, 1803, n. syn. [Stratiomyidae]; Itonida Bezzi, 1908 under Cecidomyia Meigen, 1803, n. syn. [Cecidomyiidae]; Lampetia Meigen in Hendel, 1908 under Merodon Meigen, 1803, n. syn. [Syrphidae]; Laphria Bezzi, 1907 under Laphria Meigen, 1803, n. syn. [Asilidae]; Lapria Bezzi, 1907 under Laphria Meigen, 1803, n. syn. [Asilidae]; Larvaevora Meigen in Hendel, 1908 under Tachina Meigen, 1803, n. syn. [Tachinidae]; Liriope Meigen in Hendel, 1908 under Ptychoptera Meigen, 1803, n. syn. [Ptychopteridae]; Lycoria Latreille, 1802 under Sylvicola Harris, 1776, n. syn. [Anisopodidae]; Melusina Meigen in Hendel, 1908 under Trichocera Meigen, 1803, n. syn. [Trichoceridae]; Musidora Meigen in Hendel, 1908 under Lonchoptera Meigen, 1803, n. syn. [Lonchopteridae]; Noeza Meigen in Hendel, 1908 under Hybos Meigen, 1803, n. syn. [Hybotidae]; Omphrale Meigen in Hendel, 1908 under Scenopinus Latreille, 1802, n. syn. [Scenopinidae]; Pales Bezzi, 1906 under Nephrotoma Meigen, 1803, n. syn . [Tipulidae]; Penthesilea Meigen in Hendel, 1908 under Blera Billberg, 1820, n. syn. [Syrphidae]; Petaurista Meigen in Hendel, 1908 under Trichocera Meigen, 1803, n. syn. [Trichoceridae]; Phalaenula Desmarest, 1818 under Psychoda Latreille, 1797, n. syn. [Psychodidae]; Philia Meigen in Hendel, 1908 under Dilophus Meigen, 1803, n. syn. [Bibionidae]; Phryne Meigen in Hendel, 1908 under Sylvicola Harris, 1776, n. syn. [Anisopodidae]; Polymeda Meigen in Hendel, 1908 under Erioptera Meigen, 1803, n. syn. [Limoniidae]; Polyxena Meigen in Hendel, 1908 under Cordyla Meigen, 1803, n. syn. [Mycetophilidae]; Potamida Hendel, 1903 under Clitellaria Meigen, 1803, n. syn. [Stratiomyidae]; Rhodogyne Meigen in Hendel, 1908 under Gymnosoma Meigen, 1803, n. syn. [Tachinidae]; Salmacia Meigen in Hendel, 1908 under Gonia Meigen, 1803, n. syn. [Tachinidae]; Scathophaga Meigen, 1803 under Scopeuma Latreille, 1802, n. syn. [Scathophagidae]; Coremacera Rondani, 1856 under Statinia Latreille, 1802, n. syn. [Sciomyzidae]; Tendipes Meigen in Hendel, 1908 under Chironomus Meigen, 1803, n. syn. [Chironomidae]; Titania Meigen in Hendel, 1908 under Chlorops Meigen, 1803, n. syn. [Chloropidae]; Trepidaria Meigen in Hendel, 1908 under Calobata Meigen, 1803, n. syn. [Micropezidae]; Tritonia Meigen in Hendel, 1908 under Temnostoma Le Peletier & Audinet-Serville, 1828, n. syn. [Syrphidae]; Tubifera Meigen in Hendel, 1908 under Eristalis Latreille, 1804, n. syn. [Syrphidae]; Urophora Robineau-Desvoidy, 1830 under Euribia Latreille, 1802, n. syn. [Tephritidae]; Zelima Hendel, 1903 under Xylota Meigen, 1822, n. syn. [Syrphidae]; Zelmira Meigen in Hendel, 1908 under Orfelia Costa, 1857, n. syn. [Keroplatidae].        The following three names have not been found to be synonymous with any other taxon, and are treated here as nomina dubia: Orithea Meigen in Hendel, 1908; Salpyga Meigen in Hendel, 1908; Titia Meigen in Hendel, 1908 (preoccupied).      The following four names are found to be senior synonyms of more commonly used genus-group names: Euribia Latreille, 1802 of Urophora Robineau-Desvoidy, 1830, n. syn. [Tephritidae]; Pelopia Latreille, 1802 of Ablabesmyia Johannsen, 1905, n. syn.; Scopeuma Latreille, 1802 of Scathophaga Meigen, 1803, n. syn. [Scathophagidae]; Statinia Latreille, 1802 of Coremacera Rondani, 1856, n. syn. [Sciomyzidae]. If they are construed as threatening stability of nomenclature and/or taxonomy, applications to the ICZN Commission may be warranted to request suppression of these names in favor of their junior synonyms.